Nurses\' Experiences of the Hospital Information Systems - Nahid Dehghan Nayeri; Mona Mohammadi Firouzeh; Khatereh Seylani (Tehran University of Medical Sciences, 2015)
Background & Aim: With regard to the i ncreasing trends of information and complexities of health organizations , using of a dvanced tools and computers is necessary . Hospital staff is key members to develop health information systems, because they play not only a major role in the management of system, but also in the development, implementation and evaluation of the system. Since the evaluation of information systems is not possible without analyzing of the experiences and users chr('39') views, thus the aim of this study was to explore nurseschr('39') experiences of the hospital information systems .   Methods & Materials: In this qualitative study, we investigated the nurseschr('39') experiences of the application of hospital information systems for the rich and deep understanding of the phenomenon . The c onventional content analysis was used to collect and analyze the data . Face- to-face and semi- structured interviews were conducted with participants to achieve full saturated information. Saturation was achieved with 18 interviews .    Results: The emerging themes were gradual system evolution, , audit and responsibility, security, effectiveness and accessibility .   Conclusion: Nurseschr('39') experiences were positive with the applying of the Health Information Systems. The negative experiences of the nurses were related with the application of the system and redundant work, not the system itself. Regarding to participants need, it is recommended that the system should be extended to other duties such as reporting so that more effective use of the system in order to improve the quality.